"Stuck between a Rock and a Hard Place": How Mental Health Nurses Experience Psychosocial interventions in Irish Mental Health Care Settings - De Vries, Jan; Mc Cann, Edward (My University, 2020)
Traditionally, the focus for mental health service delivery in Ireland has involved a medically orientated approach. This research has taken place at a time when mental health professionals are now assumed to provide recovery-orientated care by statute as well as policy. Within a recovery practice, psychosocial interventions (PSI) are recognised and recommended internationally as they primarily focus on improving a client’s mental health and preventing relapse, thus adopting a biopsychosocial approach. This study explored trained MHNs’ experiences of using PSI in their care of persons with a mental health problem. Consistent with the goal of understanding experience, a multiple case study methodology guided the study and situated within an interpretive paradigm. Data were gathered using semi-structured interviews with 40 PSI-trained MHNs and analysed thematically. Three overarching themes emerged: PSI-trained MHNs’ understanding and use of PSI; facilitating factors supporting the use of PSI by PSI-trained MHNs and obstacles limiting the use of PSI by PSI-trained MHNs. Overall, the findings conveyed that participants were receptive toward PSI, but cited many common obstacles that curtailed their daily PSI work. Also, a supportive organisational culture where clinical leadership and clinical supervision were available alongside PSI guidelines determined if PSI were implemented.
PUBLISHED
https://doi.org/10.1111/jpm.12702
Keywords: Psychosocial interventions; Mental health; Mental health nurses; Community; Inpatient; Inclusive Society; MENTAL HEALTH CARE PROFESSIONAL; Mental health nursing; Psychosocial Interventions; Mental Health/Psychosocial disability; Education; Health